Tools for analysis of business processes – a comparative analysis - Janicki, Jakub; Wójcik, Ernest (Journal of Computer Sciences Institute, 2021)
This article discusses topics in the field of business analysis, which is the basic element of the operation of modern organizations. The aim of this publication is to present and evaluate four selected tools for modeling business diagrams in BPMN notation. As part of the introduction to the topic, business processes were characterized, their analysis was defined, and the reader was introduced to the BPMN notation and the tested tools. The research methodology and its course were also defined. Then, the research was carried out in accordance with the adopted methodology. The conclusion of this work was the result of the research together with the analysis. Finally, the conducted experiments were summarized together with conclusions.